Enhancing supply chain performance through collaborative planning, forecasting, and replenishment - Singhry, Hassan Barau; Abd Rahman, Azmawani (Emerald Publishing, 2019)
Purpose Despite the importance of collaborative planning, forecasting, and replenishment (CPFR), its influence on supply chain innovation capability (SCIC) and supply chain performance (SCP) has not been sufficiently examined. The purpose of this paper is to examine the antecedence of SCP through CPFR and SCIC.